2020
DOI: 10.7554/elife.59733
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a neural stem cell transcriptional program in parenchymal astrocytes

Abstract: Adult neural stem cells, located in discrete brain regions, generate new neurons throughout life. These stem cells are specialized astrocytes, but astrocytes in other brain regions do not generate neurons under physiological conditions. After stroke, however, striatal astrocytes undergo neurogenesis in mice, triggered by decreased Notch signaling. We used single-cell RNA sequencing to characterize neurogenesis by Notch-depleted striatal astrocytes in vivo. Striatal astrocytes were located upstream of neural st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 43 publications
(65 reference statements)
5
46
0
2
Order By: Relevance
“…Using pseudotime analysis, a powerful approach for revealing lineage trajectories (27, 28), we found that the niche astrocytes triggered the neurogenetic process rather than the qNSCs. Our results are consistent with a recent study suggesting that the parenchymal astrocytes initiate neurogenesis before NSC activation (10). In addition, we detected an early aNSC differentiation stage prior to the activation of qNSCs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Using pseudotime analysis, a powerful approach for revealing lineage trajectories (27, 28), we found that the niche astrocytes triggered the neurogenetic process rather than the qNSCs. Our results are consistent with a recent study suggesting that the parenchymal astrocytes initiate neurogenesis before NSC activation (10). In addition, we detected an early aNSC differentiation stage prior to the activation of qNSCs.…”
Section: Discussionsupporting
confidence: 94%
“…In spite of this, recent efforts are continuing to enrich the diversity of NSCs and progenitors harbored in the heterogeneous pool (9), whereas their lineage trajectories and the delicate intercellular communications are not well understood. Jens et al recently proposed that the striatal astrocytes were latent NSCs that triggers the genesis of neuronal lineage cells upstream of NSCs (10). However, whether niche astrocytes reprogramming was the initial stage of neurogenesis in the SVZ remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive astrocytes isolated from injured brains gave rise to neurospheres in vitro ( Buffo et al, 2008 ; Shimada et al, 2012 ; Sirko et al, 2015 ). In vivo , cortical astrocytes reproduced a neurogenic response in transgenic mice with Rbpj-κ-depleted astrocytes submitted to traumatic brain injury ( Zamboni et al, 2020 ) and reactive astrocytes activated a neurogenic program after stroke in Notch-depleted striatal astrocytes transgenic ( Magnusson et al, 2020 ; Santopolo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a subpopulation of astrocytes was found positively marked, suggesting a local regulation of fatty acid production that could be possibly exploited for signaling or expansion of local membranes in astrocytes ( Sakers et al, 2017 ). Furthermore, it has been recently shown that, while undergoing a neurogenic program, some astrocytes need to upregulate genes encoding for enzymes essential for lipid metabolisms, including Elovl5 ( Magnusson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%